Power Asymmetries and the Exercise of Authority in Paid Domestic Work [Asimetrías de Poder y el Ejercicio de la Autoridad en el Trabajo Doméstico Pagado] - Fernandez-Ossandon, R (Universidad Autonoma del Estado de Mexico, 2021)
The present article aims to stress the assumptions underlying the notion of power in studies on paid domestic work and proposes to include an empirical analysis of the management of power asymmetries through the exercise of authority. The methodology of the article bases on the review and analysis of theoretical and empirical texts on the notions of power and authority in gender studies in general, and studies on domestic work in particular, in particular emphasizing the Chilean context. The analysis shows the relevance of stressing the notion of power as domination and makes a proposal for the study of the exercise of authority on the basis of empirical investigation on the affective and intimate relationships between employers and domestic workers. © 2021 Universidad Autonoma del Estado de Mexico. All rights reserved.